The influence of absorptive capacity, sources of information and technological acquisition in the technological innovation breadth of manufacturing companies - Del Carpio Gallegos, Javier (2018)
This article is an approach to new definitions of materiality as applied to corporate performance and disclosure practices. Over time, the materiality lens will have implications for multiple operating areas. They will range from; risk and compliance to strategy setting, corporate policy and governance, management practices including stakeholder engagement, and even human resource management. In the second part there is a presentation of the definitions, scope and perspectives of materiality according to six relevant standard-setters in the field of sustainability reporting. Finally there is the presentation of how materiality is reported according to the six biggest groups of quoted companies in Spain.